DERIVATIONAL MORPHEMES IN A MOVIE SCRIPT OF THE AVENGERS WRITTEN BY JOSS WHEDON - Baiatun Nisa; Lia Nurmalia; Firdha Rizka Amelia; Unpris Yastanti (IJOLTL (Indonesian Journal of Language Teaching and Linguistics), 2023)
This research is aimed to give contribution about the process of word formation, especially derivational morphemes. Descriptive qualitative method is applied in this research by collecting data, then observing and analyzing it descriptively. The data are taken from a movie script entitled The Avengers.The results obtained 68 are found in the script, with detail findings are most derivational morphemes are formed by suffixes 41 data (60.3%), followed by prefix 22 data (32.4%), and infix 5 data (7.3%). The findings imply the process of word formation is by identifying the root and elaborating its formation whether prefix, suffix or infix, so one word can create new word and meaning